Diabetes mellitus and tuberculosis: pattern of tuberculosis, two‐month smear conversion and treatment outcomes in Guangzhou, China. Issue 11 (23rd September 2013) - Mi, Fengling; Tan, Shouyong; Liang, Li; Harries, Anthony D.; Hinderaker, Sven G.; Lin, Yan; Yue, Wentao; Chen, Xi; Liang, Bing; Gong, Fang; Du, Jian
Abstract: Objective: There is a high burden of both diabetes (DM) and tuberculosis (TB) in China. We evaluated the association between DM and the pattern of disease, 2‐month sputum smear conversion and treatment outcomes of patients with TB in Guangzhou, China. Method: All patients registered with TB from September 2011 to June 2012 were screened for DM and assessed for treatment outcomes in relation to presence or absence of DM and quality of DM control using patient registers, treatment cards and electronic record systems. Results: There were 1589 patients with TB of whom 189 (12%) had DM. Among those with DM, there was a significantly higher proportion of men, persons aged 35 years and older and persons with smear‐positive pulmonary tuberculosis (PTB) ( P  < 0.01). In patients with DM and new smear‐positive PTB, there was a higher proportion who had positive sputum smears at 2 months (21.7% vs . 5.6%, RR 3.85, 95%CI 2.24–6.63), who were lost‐to‐follow‐up (5.2% vs . 1.7%, RR 3.23, 95%CI 1.08–9.63) and who failed treatment (10.3% vs . 2.3%, RR 4.46, 95%CI 1.96–10.18) compared with patients who had no DM. There was no significant association between these adverse outcomes and DM control as measured by 2 and 6‐month fasting blood glucose. Conclusion: Diabetes mellitus in new smear‐positive patients with PTB was associated with failure to sputum smear convert at 2 months and adverse treatment outcomes of loss‐to‐follow‐up and failure. Further research is needed to understand the reasons for these findings and to determine whether the current length of treatment of 6 months is adequate.